Characterization of an inductively coupled plasma produced in argon at 13.56 MHz / Lim Ai Nuan - Lim, Ai Nuan (2010)
The electrical and plasma characteristics of radio frequency (13.56 MHz) inductively coupled argon plasma (RF ICP) were studied in this project. On the electrical breakdown properties, the breakdown voltage has a general appearance of Paschen’s curve and the minimum is achieved at 0.1 mbar. After ignition, two modes of discharge exist, namely, the E mode at low RF power and H mode at high RF power. Mode transition that occurs is accompanied by abrupt changes in both electrical and plasma characteristics. Hysteresis is observed in the mode transitions and has a minimum at 0.1 mbar. The resistance reflected into the electrical circuit due to H mode plasma is 9.8 times higher when compared to E mode (Rp= 0.10±0.01) Ω. Therefore, the impedance matching scheme used is most efficient at E mode where the antenna coil resistance Ra is (1.12±0.01) Ω. Ra doubles in the H mode. However, the transfer of power is more efficient in the H mode. This efficiency is reflected in the much higher electron density of ne = (3.6−12.2)×1017 m−3 measured in the H mode at 0.10±0.1 mbar. Consequently, the increased electron collisions tend to lower the electron temperature Te in the H mode (1.7−2.0 eV) as compared to that in E mode (Te = 2.3-2.8 eV). The measured electron energy distribution function EEDF in H mode is inclined towards Maxwellian-type especially at 200 W. From the radial distribution of plasma properties, it is deduced that E mode discharge is relatively more uniform and diffuse.